Planning by Cycle Parking Type: A Cycle Parking Preference Typology for Cyclists - Caulfield, Brian; Egan, Robert; Dowling, Conor Mark (My University, 2022)
The purpose of this study is to develop a typology of cycle parking type preferences among a sample who have access to a cycle and travel within or to the electoral county of Dún Laoghaire-Rathdown, Ireland. Valid online survey questionnaire data were gathered from 574 respondents. First, using Principal Components Analysis, we reduced 11 cycle parking type preference variables into three cycle parking type components: Open, Locked and Guarded. Second, analysing cycle parking type preference data for each component, we implemented both a hierarchical and k-means cluster analysis to generate a five cluster solution comprising of Informal, Open, Any, Accessible and Secure cycle parking preference clusters. Third and last, we profiled our five cluster solution, examining the demographic composition, current and hypothetical mobility/cycling practices, and perceptions of cycle parking in Dún Laoghaire-Rathdown at present for each of the clusters. We conclude that our cycle parking type preference typology could be used to inform local and national cycle parking policy and planning efforts in several ways: i) targeting clusters that may yield the greatest increase in aggregate cycle ridership, ii) catering for clusters on the basis of enhancing cycle equity for those demographically underrepresented in cycle ridership and/or potentially marginalised in cycle infrastructure planning efforts, and iii) providing for clusters on the basis of strategically promoting particular cycle-activities (Cass and Faulconbridge, 2016), such as cycle-shopping, and end use practices (Spurling, 2020) that may require unique forms of cycle parking.
PUBLISHED
Keywords: Cycle parking; Bicycle parking; Transport planning; Typology; Cluster analysis; Parking policy; Smart & Sustainable Planet; Environmental Impacts of Transport; Transport